Implementasi Prosedur Penyiapan Kamar Tamu Di Hotel Golden Tulip Jineng Resort Bali - Luigi Viriya Kumara; I Wayan Seniartha; Ni Nyoman Suci Arthini (Journal of Hospitality Accommodation Management (JHAM), 2023)
This study aims to determine the implementation of the application of guest room preparation at the Golden Tulip Jineng Resort Bali Hotel. This research is carried out to find out things of a negative nature or shortcomings that need to be corrected. To obtain data, data collection techniques are applied in the form of observations and interviews. The analysis method used is descriptive qualitative, in this writing the data obtained such as: the results of observations regarding the implementation of the implementation of guest room preparation at the Golden Tulip Jineng Resort Bali Hotel which refers to the established standard operating procedures. The results of this study show that the implementation of the implementation of guest room preparation at the Golden Tulip Jineng Resort Bali Hotel is not satisfactory. Golden Tulip Jineng Resort Bali Hotel needs to improve several services by the Room Attendant to always follow the standard operating procedures set from the hotel. This aims to reduce the number of guest complaints.